Principal's Leadership in Improving Teacher Work Discipline at SMA Negeri 1 Airmadidi - Tuerah, Paulus Robert; Singal, Cicilia Indry; Patylima, Jesika Berta; Rumondor, Susana Silvia; Korompot, Sudarmin (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This study aims to know and describe the Principal's leadership role in improving teacher work discipline and find out the obstacles to the Principal's leadership role in improving teacher work discipline at SMA Negeri 1 Airmadidi. This research is descriptive with qualitative research types and purposive sampling techniques. The Headmaster has five parts and two obstacles to improving teacher discipline. The results showed that the Principal of SMA Negeri 1 Airmadidi acted as a leader with planning and thinking, as a leader by creating cooperation between teachers, as an educator by creating a curriculum, as an administrator by installing managed facilities and infrastructure, as financial management as motivation through motivation in a profitable school environment. Obstacles to school leaders in improving teacher work discipline include teachers who need more discipline in carrying out their duties. Improving work discipline and inadequate school facilities and infrastructure is also challenging.